Group eye movement desensitization and reprocessing (EMDR) in chronic pain patients - Vock, Stephanie; Delker, Anna; Rinderknecht, Janna; Engel, Felicitas; Wieland, Sebastian; Beiner, Eva; Friederich, Hans-Christoph; Jarero, Ignacio Nacho; Seidler, Günter H.; Tesarz, Jonas (Frontiers in Psychology, 2024)
The prevalence of chronic pain is increasing, and conventional pain therapies often have limited efficacy in individuals with high levels of psychological distress and a history of trauma. In this context, the use of Eye Movement Desensitization and Reprocessing (EMDR), an evidence-based psychotherapy approach for the treatment of posttraumatic stress disorder, is becoming increasingly important. EMDR shows promising results, particularly for patients with pain and high levels of emotional distress. Although group therapy is becoming increasingly popular in pain management, EMDR has mainly been studied as an individual treatment. However, a systematic review suggests that group therapy can be an effective tool for improving mental health outcomes, especially when trauma is addressed together. Based on these findings, an outpatient EMDR group program was developed for patients with chronic pain. The program consists of a total of four treatment days with 5 to 5.5 hours therapy sessions each day and provides patients with a supportive environment in which they can learn effective pain management strategies and interact with other patients with similar experiences. Initial pilot evaluations indicate high efficacy and adequate safety for patients with chronic pain.